Village agricultural practices: Baseline findings from the FRESH End-to-End Evaluation - Reynolds, Elise; Mwombeki, Wiston; Kinabo, Joyce; Jeremiah, Kidola; Malindisa, Evangelista; Olney, Deanna K.; Kumar, Neha; Bliznashka, Lilia (International Food Policy Research Institute, 2024)
Fruit and vegetable (F&V) production is growing rapidly across Tanzania, particularly among rural smallholder farmers. Increased F&V production could help improve diets within these communities and beyond. However, farmers face barriers in increasing production due to lack of access to key agricultural inputs including seeds, fertilizers, pesticides, and irrigation, among others. Farmers also require financing to access these inputs as well as extension services to increase training and use of these agricultural practices. In response to these needs, the FRESH end-to end approach implemented in two regions in Northern Tanzania aims to increase the desirability, affordability, accessibility, and availability of F&V through interventions at various points of the food system, including demand creation, food environments and supply (production and post-harvest management). More information on the FRESH end-to-end approach and evaluation can be found in the FRESH Research Brief 1. The effectiveness of the FRESH end-to-end approach in improving vegetable production and F&V intake is being assessed through an impact evaluation conducted in 33 villages across 5 districts in the Arusha and Kilimanjaro regions of Northern Tanzania. In this research brief, we describe findings on the baseline characteristics of the villages included in the evaluation with a specific emphasis on agricultural inputs, F&V storage and processing facilities, and other relevant agricultural characteristics. We explore these characteristics for the full sample of 33 villages, as well as at the district and regional levels.